DETERMINASI PENGUNGKAPAN CORPORATE SOCIALRESPONSIBILITY PADA PERUSAHAAN DI INDONESIA - Oddy Sonata (2022)
This study aims to empirically examine the effect of intellectual capital, institutional ownership, foreign ownership, and CEO duality on the disclosure of corporate social responsibility in energy and basic materials companies listed on the Indonesia Stock Exchange for the 2017-2020 period. This study uses quantitative methods with secondary data in the form of annual reports and company sustainability reports through the website www.idx.co.id or each company. The sample in this study was 20 energy and basic materials companies for the 2017-2020 observation year, using the purposive sampling method. The data analysis technique used is the model specification test, classical assumption test, and hypothesis testing with STATA version 16. The results show that (1) Intellectual capital has a significant negative effect on corporate social responsibility disclosure, (2) institutional ownership has no effect on corporate social disclosure. social responsibility, (3) foreign ownership has no effect on the disclosure of corporate social responsibility, and (4) CEO duality has no effect on the disclosure of corporate social responsibility. Suggestions for companies and investors to pay attention to intellectual capital and disclosure of corporate social responsibility that exist in the company. For further research to use renewable measurements for intellectual capital such as M-VAIC, add control variables such as firm size, profitability, or leverage, and add population such as non-financial sector and year of observation.